NAVIGATING THE MULTIFACETED LANDSCAPE OF DIGITAL TRANSFORMATION IN HIGHER EDUCATION: TECHNOLOGICAL ADOPTION, PEDAGOGICAL SHIFTS, AND SOCIOECONOMIC IMPLICATIONS IN INDONESIA - Hety Devita; Zainuddin; Yance Manoppo; Husna Amin; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2023)
The landscape of higher education is undergoing a profound transformation driven by the omnipresence of digital technology. This research delves into the multifaceted dimensions of digital transformation in Indonesian higher education, focusing on technological adoption, pedagogical shifts, and socioeconomic implications. Our findings, derived from a diverse group of stakeholders within the sector, illuminate a complex tableau of opportunities and challenges. The research reveals that approximately 78% of respondents affirm integrating digital tools and platforms in their academic institutions, marking a substantial technological adoption. This adoption encompasses a remarkable 65% of respondents reporting the presence of Learning Management Systems (LMS), reflecting the centrality of technology in content delivery and student engagement. Pedagogical shifts emerge as a significant theme, with 72% of respondents acknowledging changes in their teaching methods. A noteworthy 61% employ blended learning strategies, ushering in a shift from traditional lecture-based pedagogies to interactive, student-centered models. These transformations underscore the commitment to enhancing the student learning experience and fostering critical thinking. Socioeconomic implications cast a dynamic shadow, with 58% of respondents recognizing the potential of digital education to bridge socioeconomic gaps. However, concerns expressed by 42% regarding the digital divide highlight the challenges in ensuring equitable access to educational opportunities. As higher education in Indonesia continues to navigate the digital terrain, this research underscores the need for a nuanced approach that leverages technological opportunities while addressing the challenges of equitable access and pedagogical innovation.